2019
DOI: 10.1021/jacs.9b01882
|View full text |Cite
|
Sign up to set email alerts
|

Growth Kinetics of Individual Co Particles Ex-solved on SrTi0.75Co0.25O3-δ Polycrystalline Perovskite Thin Films

Abstract: A precise control of the size, density, and distribution of metal nanoparticles dispersed on functional oxide supports is critical for promoting catalytic activity and stability in renewable energy and catalysis devices. Here, we measure the growth kinetics of individual Co particles ex-solved on SrTi0.75Co0.25O3‑δ polycrystalline thin films under a high vacuum, and at various temperatures and grain sizes using in situ transmission electron microscopy. The ex-solution preferentially occurs at grain boundaries … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
97
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 86 publications
(108 citation statements)
references
References 43 publications
9
97
1
Order By: Relevance
“…6 and suggests that the growth rate of the particles is limited by the rate of iron reduction at the surface of LSF. This result is also in line with studies in literature, which also found a reactioncontrolled growth of metallic particles exsolved from perovskite-type oxides 21,34 . However, for the exsolution of Fe 0 from LSF a distinction between strain-and reactant-controlled is not possible, but since Fe is the only element on the B-site of LSF and its high concentration does not change drastically upon exsolution, a minor (if any) role of the reactant concentration for the particle growth rate can be assumed.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…6 and suggests that the growth rate of the particles is limited by the rate of iron reduction at the surface of LSF. This result is also in line with studies in literature, which also found a reactioncontrolled growth of metallic particles exsolved from perovskite-type oxides 21,34 . However, for the exsolution of Fe 0 from LSF a distinction between strain-and reactant-controlled is not possible, but since Fe is the only element on the B-site of LSF and its high concentration does not change drastically upon exsolution, a minor (if any) role of the reactant concentration for the particle growth rate can be assumed.…”
Section: Resultssupporting
confidence: 93%
“…6a and the entire data set of particle growth-in-situ and ex-situ-was analysed by employing kinetic models described in literature (for details please refer to the Methods section) 33 . As a result, we suggest a reaction-controlled growth with a significant effect of the strain of the particles, in line with studies focussing on the kinetics of the exsolution process 21,34 . Interestingly, this increase of the exsolution particle size is not reflected in the current-voltage curve, since differences of reaction rates (i.e., currents) for different times (e.g., at 9 and 92 min in Fig.…”
Section: Resultssupporting
confidence: 88%
“…In situ TEM has been employed to provide insights at nanoscale into the exsolution of metallic nanoparticles in perovskites under reducing atmosphere . Herein, we use in situ STEM and ESEM to provide direct insight into the exsolution/reincorporation of CoFe alloy nanoparticles under both reducing and oxidizing atmospheres ( Figure and Figure S3, Supporting Information).…”
Section: Figurementioning
confidence: 99%
“…[ 7 ] Furthermore, the metal NPs produced by ex‐solution are strongly bound to the host oxide and thus have excellent thermal and chemical stability. [ 8,9 ] Accordingly, thanks to these advantages, the ex‐solution process is now being applied in high‐temperature chemical and electrochemical applications, such as solid oxide fuel cells, [ 10 ] electrolyzers, [ 11 ] and oxidation catalysts. [ 12 ]…”
Section: Figurementioning
confidence: 99%